Hypertrophy Determination of H9c2 Cardiomyoblast Cell Line Using Wright-Giemsa Staining: An Experience in Developing an Acceptable and Easy-to-handle In-vitro Protocol - Fadhillah, Muhamad Rizqy; Arozal, Wawaimuli; Wibowo, Heri; Bustami, Arleni; Sukmawati, Dewi; Kusmardi, Kusmardi; Triana, Novi; Khatimah, Nurul Gusti (Majalah Patologi Indonesia, 2024)
Introduction Cell-size area (CSA) becomes the standard parameter routinely tested in vitro for cardiac hypertrophy studies. Thus, staining is an essential tool for this purpose. As reported in a previous study, immunofluorescence staining is an established method for CSA. However, because it is expensive and requires a specialized microscope, e.g., immunofluorescence or confocal microscope, it is not applicable in a laboratory with limited equipment. Wright-Giemsa staining is a standard procedure in hematology laboratories and is inexpensive and convenient. Here, we shared our experience developing a CSA determination protocol using Wright-Giemsa in H9c2 cardiomyoblast. Methods The viability tests were performed on H9c2 to determine the effective dosage of angiotensin II and Irbesartan (standard drug). The H9c2 were divided into three groups: the control group (without either angiotensin II or irbesartan), the negative control (with angiotensin II), and the positive control (with angiotensin II and Irbesartan), triplicate for each group. The cells then are acclimatized overnight, serum-starved for one day, and incubated with angiotensin and irbesartan for 48 hours. Lastly, Wright-Giemsa was observed using a light microscope in three fields. The CSA was determined by three independent observers blindly, statistically different if the p<0.05 using ANOVA ways or Kruskal-Wallis. Results After the H9c2 induced by angiotensin-II 1 μM and Irbesartan 1μM, we found the CSA significantly differed among each group (p<0,0001). The negative control has a higher median and interquartile range (IQR) CSA (10.78 (6.79) um2) compared to the control group (median (IQR) 7.27 (4.91) um2) and positive control (median (IQR) 7.849(5.31) um2). Conclusion It can be concluded that the Wright-Giemsa might help determine the CSA for in-vitro hypertrophic studies.